Infrastructures of Reality: Metaverse Stories, Spaces, Bodies - Hesselbein, Chris; Bory, Paolo (Springer Nature, 2025)
This open access book focuses on two dimensions of the development of the metaverse that are crucial to ‘reality’, namely spatiality and embodiment. Metaversal technologies are thought to fundamentally affect both our spaces and bodies, which are two central aspects of the constitution of social reality. Both spatiality and embodiment are core elements of world-making that are being pulled into the ambit of metaversal projects. On the one hand, metaversal technologies are profoundly spatial in the sense that they render space in virtual form or overlay digital layers onto pre-existing physical spaces. On the other hand, metaversal technologies are directly geared towards the body in that they not only seek to extend or expand our embodied senses and emplace our bodies in virtual spaces, but they also seek to capture their behaviours and actions on a far more granular level. This can create new opportunities in terms of work, social interaction, and leisure, but can also open our bodies up to new, tech-driven interventions and control. Whether in the form of VR or AR, such technologies not only reproduce space but also rely on making spaces more legible and open to automated interventions. Taken together, the ‘metaversification’ of spaces and bodies gives rise to crucial questions about the goals and implications of metaversal developments by large technology companies and about the relationship between the developments of the metaverse and AI systems. Drawing on our combined background and expertise in Science and Technology Studies and the History of Media and Communication, we critically analyse the development of metaversal technologies and platforms by discussing a broad set of developments and examples from a wide range of technology and gaming companies. Written in clear, concise, and accessible language, and combining and applying novel theoretical frameworks and concepts to a currently emergent phenomenon, this book will find a large audience not only within academic and professional circles but also in popular culture.